TEORI SOSIALISASI KEBIJAKAN PENDIDIKAN - Hidayat, Wahyu; Ramadhana, Ari; Suryana, Ardi (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2023)
Abstract Socialization is the most important process that we consciously or unconsciously live in our daily lives. Education policy is very important related to the morals of students. Aims to find out how to socialize education policy; knowing the stages of education policy socialization of education policy. This research was carried out with a qualitative descriptive approach seen from the point of view of education policy socialization, an approach that was in accordance with the circumstances found. The results of this study indicate that; there are several stages that need to be considered in the educational policy socialization process, namely: 1) the preparation stage (play stage), and 2) the action stage (game stage). Education policies that have been formulated can be disseminated using various media, both in the form of communication media such as posters, brochures, banners, and billboards, as well as through electronic media, such as optical discs (compact disks or DVD), sosial media, internet, radio and television.